Propagation of vortex laser beams of a metal resonator - Degtyarev, A. V.; Dubinin, M. M.; Maslov, V. A.; Muntean, K. I.; Svystunov , O. O. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2024)
Background: The problem of radiation propagation of vortex laser beams of a metal waveguide laser is considered. The results of the propagation of such beams have a wide range of potential applications, from imaging and spectroscopy to communication, sensing, biomedicine, and solving problems related to the interaction of electromagnetic waves with matter: diagnostics of thin films, surfaces of materials, various biological objects, as well as astronomy and space research.The aim of the work is to obtain analytical expressions for the description of non-paraxial mode diffraction of the waveguide metal resonator of a terahertz laser during their interaction with a spiral phase plate and to study the physical features of the obtained vortex beams during their propagation in free space by means of numerical modeling.Materials and methods: The Rayleigh-Sommerfeld vector theory was used to study the propagation of vortex laser beams in the Fresnel zone, which were excited by the modes of a metal waveguide quasi-optical resonator.Results: Analytical expressions were obtained to describe the non-paraxial mode diffraction of the metal waveguide resonator of a terahertz laser. Also, with the help of numerical modeling, the physical features of emerging vortex beams during their propagation in free space were investigated.Conclusion: In free space, the spiral phase plate for the excitation of the TE11 mode from the profile with the intensity maximum in the center (n = 0) forms an asymmetric ring with two maxima (n = 1, 2). For the TE01 excitation mode, the initial ring (n = 0) structure of the field strength is transformed into a structure with maximum radiation intensity in the center (n = 1), and then again into a ring (n = 2). The phase front of the beam for the Ey component linearly polarized along the y axis of the TE11 mode changes from spherical to helical with one singularity point on the axis. In the phase profile of the transverse components of the TE01 azimuthally polarized mode, a section with two and three off-axis points of phase singularities appears.